Taliglucerase alfa in the longterm treatment of children and adolescents with type 1 Gaucher disease: the Albanian experience - Cullufi, Paskal; Tomori, Sonila; Velmishi, Virtut; Gjikopulli, Agim; Akshija, Ilir; Tako, Aferdita; Dervishi, Ermira; Hoxha, Gladiola; Tanka, Marjeta; Troja, Erjon; Tabaku, Mirela (Frontiers in Pediatrics, 2024)
Introduction. Enzyme replacement therapy is already recognized as the gold standard of care for patients with Gaucher disease. Taliglucerase alfa is one of the three alternatives recommended for treatment of Gaucher disease in children and adults. Aim: This study aims to evaluate the long-term efficacy and safety of Taliglucerase alfa in children and adolescents with Type 1 Gaucher disease. Patients and Methods: Over a six-year period, we monitored the efficacy of continuous treatment in 10 patients by assessing various parameters, including hemoglobin concentration, platelet count, liver and spleen volume, bone mineral density, glucosylsphingosine level, chitotriosidase activity, and growth parameters. Safety was evaluated by immunogenicity and adverse event monitoring. Results: The mean age of patients was 13.4±3.6 years and the treatment duration was 60.24 ±13.4 months. From baseline to endlineend line the parameters change as follows: hemoglobin concentration improved from 12.7 (±1.3) to 14.6 (±1.5) and platelet count from 180 (±74) to 198 (±79). The spleen volume, was reduced by 46% (p=0,007). The chitotriosidase activity decreased from 4019.7 (±3542.0) nmoles/mL/hr to 2039.5 (±1372.2) nmoles/mL/hr (46% reduction). Glucoylsphingosine level dropped from 119.2 (±70.4) ng/ml to 86.2 (±38.1) ng/ml, indicating a reduction of 28%. Bone mineral density Z-score, improved from -1.47 (±1.76) to -0.46 (±0.99) (69.7% reduction). Out of the 1301 total administrations, our patients reported only 37 (2.8%) infusion-related adverse events which were mild and transitory. Conclusion: Taliglucerase alfa exhibits good efficacy and a safe profile in the treatment of children and adolescents with Type 1 Gaucher disease.